On the emissions-inequality trade-off in energy taxation: Evidence on the German car fuel tax - Dragana Nikodinoska; Carsten Schröder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
By using estimates from an Almost Ideal Demand System (AIDS), we investigate how the German energy tax on car fuels changes the private households-CO2 emissions, living standards, and post-tax income distribution. Our results show that the tax implies a trade-off between the aim to reduce emissions and vertical equity, which refers to the idea that people with a greater ability to pay taxes should pay more.
Keywords: C31; D12; D63; H22; H23; I3; K32; Q21; 330; energy taxes; environmental taxes; energy demand; emissions; tax incidence; redistribution; inequality